Crystallization of FcpA from Leptospira, a novel flagellar protein that is essential for pathogenesis. Issue 3 (1st March 2017) - San Martin, Fabiana; Mechaly, Ariel E.; Larrieux, Nicole; Wunder, Elsio A.; Ko, Albert I.; Picardeau, Mathieu; Trajtenberg, Felipe; Buschiazzo, Alejandro
Abstract : FcpA from Leptospira interrogans, which is essential for pathogenesis, was crystallized but proved to be recalcitrant to X‐ray diffraction studies. The orthologue from the saprophyte L. biflexa allowed three different crystal forms to be obtained that were suitable for crystallographic studies. Abstract : The protein FcpA is a unique component of the flagellar filament of spirochete bacteria belonging to the genus Leptospira . Although it plays an essential role in translational motility and pathogenicity, no structures of FcpA homologues are currently available in the PDB. Its three‐dimensional structure will unveil the novel motility mechanisms that render pathogenic Leptospira particularly efficient at invading and disseminating within their hosts, causing leptospirosis in humans and animals. FcpA from L. interrogans was purified and crystallized, but despite laborious attempts no useful X ray diffraction data could be obtained. This challenge was solved by expressing a close orthologue from the related saprophytic species L. biflexa . Three different crystal forms were obtained: a primitive and a centred monoclinic form, as well as a hexagonal variant. All forms diffracted X‐rays to suitable resolutions for crystallographic analyses, with the hexagonal type typically reaching the highest limits of 2.0 Å and better. A variation of the quick‐soaking procedure resulted in an iodide derivative that was instrumental for single‐wavelength anomalous diffraction methods.